2020
DOI: 10.1016/j.solmat.2020.110461
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the tunable carrier selectivity of atomic-layer-deposited TiOx nanolayers in crystalline silicon solar cells

Abstract: Titanium oxide (TiOx) nanolayers grown by atomic layer deposition are investigated with respect to their application as carrier selective contacts for crystalline silicon (c-Si) solar cells. Although TiOx is known to act as an electron contact, in this work the selectivity of TiOx layers is found to be widely tunable from electron to hole selective depending on deposition conditions, post-deposition treatments, and work function of the metal electrode used. Using TiOx and an intrinsic hydrogenated amorphous si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
3
22
0
Order By: Relevance
“…It has been demonstrated that the hole selectivity of the t-ALD TiO x increases with an increase of the work-function of the capping material. 23,24 Our results suggest that the relatively large work function of the capping electrode is essential to sustain the band bending created by the fixed charge in the TiO x layer. Finally, the passivation of Si surface by TiO x layer works unpinning the Fermi-level position at the TiO x /Si interface, allowing it to move toward the valence band.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It has been demonstrated that the hole selectivity of the t-ALD TiO x increases with an increase of the work-function of the capping material. 23,24 Our results suggest that the relatively large work function of the capping electrode is essential to sustain the band bending created by the fixed charge in the TiO x layer. Finally, the passivation of Si surface by TiO x layer works unpinning the Fermi-level position at the TiO x /Si interface, allowing it to move toward the valence band.…”
Section: Discussionsupporting
confidence: 90%
“…In our preliminary work, , it was shown that the t-ALD TiO x deposited under similar conditions exhibits distinct features in terms of induced band bending and surface passivation. First, it gives strong band bending of 800–900 meV for n -Si but less than 100 meV for p -Si.…”
Section: Resultsmentioning
confidence: 99%
“…Upon annealing, ALD SiO x , SiN x , AlO x , AlN x , and TiO x interlayers deposited on silicon can form negative or positive fixed charges that accumulate holes or electrons near the surface of the silicon wafer 40,47,58–62 . In dependence of the thickness of the interlayer and the annealing temperature, the band bending and the fixed charges were determined for the ALD layers before implementing them as interlayers in the polysilicon contact structures, see Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…Using plasma‐enhanced ALD, ultra‐thin SiO x , SiN x , AlO x , AlN x , and TiO x interlayers were deposited either on top of the conventional thermally‐grown SiO x or on hydrofluoric acid (HF) dipped silicon wafers at different deposition (substrate) temperatures in a FlexAL system from Oxford Instruments. As precursors, bis (diethylamino)silane (BDEAS) for SiO x 37–40 and SiN x, 41 trimethylaluminium (TMA) for AlO x 42–44 and AlN x, 45,46 and titanium isopropoxide (TTIP) for TiO x 47 were used together with oxygen (O 2 ), nitrogen (N 2 ), or nitrogen(N 2 )/hydrogen (H 2 ) plasma gases for SiO x , AlO x and TiO x, SiN x , and AlN x , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, TiO 2 has been widely used in selective contacts with c-Si solar cells and the highest conversion efficiency reached 22.5%. [25] Recently, studies have found that it also can act as a hole-selective contact with c-Si by changing the interface composition of TiO 2 /c-Si, [26,27] indicating that band bending and the position of the Fermi level play a more important role in carrier selectivity than band offsets. In contrast to the commonly studied TiO 2 , Nb 2 O 5 features excellent optical transmittance, a wide bandgap (3.3-3.8 eV), higher carrier mobility (%26 cm 2 V À1 s À1 ), [28] as well as good chemical stability, which is expected to be a superior selective contact passivating material.…”
Section: Introductionmentioning
confidence: 99%